PENGEMBANGAN MULTIMEDIA SIKUAIR DALAM MATERI SIKLUS AIR PADA SISWA KELAS 4 SDN MRICAN 2 - Dini, Fitri Aprilia; Fahmi Imron, Ilmmawati; Nurfahrudianto, Aan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was motivated by the fact that many students have difficulty understanding the water cycle material. Based on the need assessment that has been given to fourth grade students of Mrican 2 Elementary School, it shows that students consider water cycle learning difficult to understand. So from the results of the presentation, 75% of students' total scores are still below the KKTP. The objectives of this research and development are: (1) To describe the validity of Sikuair Multimedia in Water Cycle Material for Fourth Grade Students of Mrican 2 Elementary School (2) To describe the practicality of Sikuair Multimedia in Water Cycle Material for Fourth Grade Students of Mrican 2 Elementary School. (3) To describe the effectiveness of Sikuair Multimedia in Water Cycle Material for Fourth Grade Students of Mrican 2 Elementary School. This research uses the (R&D) (Research and Development) method with the ADDIE model consisting of 5 steps, namely 1) Analyze, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The subjects of this study were 29 fourth grade students of Mrican 2 Elementary School. The results of this study indicate that (1) The results of the validity test obtained 91% with a very valid category. (2) The results of the practicality test obtained a teacher's practicality score of 96%. The results of the limited student trial were 91.6% and the extensive trial was 93.7%, both student practicality scores obtained an average of 92.65%. The teacher's practicality score and the average student's practicality were included in the very practical category. (3) The results of the effectiveness test were 94.4% with a very effective category.